2009
DOI: 10.2169/internalmedicine.48.2417
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Pulmonary Diffusing Capacity in Diabetes Mellitus with Regard to Microalbuminuria

Abstract: group (p=0.006; p=0.039; p=0.003, respectively). UAE was inversely correlated with DLCO, DLCO/VA, DLCO/VA% and DLCO% (p=0.050; p=<0.001; p=0.001; p=0.004, respectively). Conclusion This study demonstrated that alveolar gas exchange capacity is significantly decreased in diabetic patients. Microalbuminuria may be one of the predictors of this decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…In addition to impairments of skeletal muscle perfusion and metabolic function, both type 1 and type 2 diabetics exhibit decreases in alveolar gas-exchange capacity (261). Notable among type 1 diabetics is a thickening of the alveolar epithelial and the capillary endothelial basal laminae, that may be expected to result in impaired gas exchange, at least when elevations in metabolic rate are present.…”
Section: Diabetes and Diabetic Ketoacidosismentioning
confidence: 99%
“…In addition to impairments of skeletal muscle perfusion and metabolic function, both type 1 and type 2 diabetics exhibit decreases in alveolar gas-exchange capacity (261). Notable among type 1 diabetics is a thickening of the alveolar epithelial and the capillary endothelial basal laminae, that may be expected to result in impaired gas exchange, at least when elevations in metabolic rate are present.…”
Section: Diabetes and Diabetic Ketoacidosismentioning
confidence: 99%
“…Patients with type 2 diabetes (DM2) might be good candidates for hyperoxic exercise training as previous research indicated that DM2 patients frequently have a reduced diffusion capacity of the lungs (8–25 %), inversely related to blood glucose levels as well as duration and severity of DM2 [ 15 17 ]. Pathophysiological mechanisms explaining the impaired pulmonary function may be micro-angiopathy, chronic inflammation and autonomic neuropathy [ 16 , 18 ] resulting in a diminished alveolar micro-vascular reserve [ 15 , 17 , 19 21 ]. Impaired alveolar gas exchange in DM2 patients has been shown to correlate with a lower and workload capacity during aerobic type of exercise [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saler et al compared DLCO between 80 healthy subjects 44 patients with type 1 DM and 68 patients with type 2 DM [170]. DLCO and the ratio of DLCO to VA were significantly decreased in patients with both types of DM, but not in the control group.…”
Section: Introductionmentioning
confidence: 99%